The features of distribution α-SMA in spleen structures in health and after intrauterine action of antigen - Talanova O.S.; Voloshyn M.A. (Морфологія, 2013)
The purpose of the study – to study features of the distribution α-SMA in the structures of the spleen in health and after intrauterine action of antigen. The objects of the study were 28 human spleens (fetuses and newborns died within the first year after birth). Spleen of children were divided into two groups: the first - stillborn fetus, which were effected by intrauterine infection, the second - fetus without intrauterine infection. In the spleen structures were identified, well as defined the distribution of mesospecified actin in trabecular cells α-SMA. The changes found in infants after prenatal action of antigen, regardless the way of injection, reflect the imbalance in terms and rates of spleen structure formation. This leads to changes in terms and rates of local immune system formation. As a result the hyperplastic processes occur in viscera.